Carrier Formation Dynamics of Organic Photovoltaics as Investigated by Time-Resolved Spectroscopy. (27th June 2012) - Yonezawa, Kouhei; Ito, Minato; Kamioka, Hayato; Yasuda, Takeshi; Han, Liyuan; Moritomo, Yutaka
Abstract : Bulk heterojunction (BHJ) based on a donor (D) polymer and an acceptor (A) fullerene derivative is a promising organic photovoltaics (OPV). In order to improve the incident photon-to-current efficiency (IPCE) of the BHJ solar cell, a comprehensive understanding of the ultrafast dynamics of excited species, such as singlet exciton (D*), interfacial charge-transfer (CT) state, and carrier (D + ), is indispensable. Here, we performed femtosecond time-resolved spectroscopy of two prototypical BHJ blend films: poly(3-hexylthiophene) (P3HT)/[6, 6]-phenyl C61 -butyric acid methyl ester (PCBM) blend film and poly(9, 9′-dioctylfluorene-co-bithiophene) (F8T2)/[6, 6]-phenyl C71 -butyric acid methyl ester (PC70 BM) blend film. We decomposed differential absorption spectra into fast, slow, and constant components via two-exponential fitting at respective probe photon energies. The decomposition procedure clearly distinguished photoinduced absorptions (PIAs) due to D*, CT, and D + . Based on these assignments, we will compare the charge dynamics between the F8T2/PC70 BM and P3HT/PCBM blend films.